Gardens of life: Multifunctional and ecosystem services of urban cemeteries in Central Europe and beyond—Historical, structural, planning, nature and heritage conservation aspects - Säumel, Ina; Butenschön, Sylvia; Kreibig, Nina (Frontiers in Environmental Science, 2023)
Cemeteries are often seen as monofunctional spaces for burial and mourning and, within the dynamically changing urban fabric, as a planning conundrum. Long periods of stability have also turned these untouched and hidden places into refugia for nature and wildlife. In booming and dense cities with high land use pressures and housing shortages, in particular, as the amount of burial ground needed per citizen decreases and burial cultures change, the cemetery has become a contested nature, as a simultaneous space of emotion, commerce and community. We revisited the diversity and ontogenesis of cemeteries, and the interactions with neighboring uses of the urban matrix. Our review demonstrates a wide range of different ecosystem services of urban cemeteries, beyond potential as hotspots of culture and biodiversity. We highlight their multifunctional character and the need for a holistic and trans-disciplinary evaluation using multistakeholder approaches to further develop cemeteries as a crucial element of sustainable urban landscapes.